Square-wave voltammetric determination of drospirenone and ethinylestradiol in pharmaceutical dosage form using square wave technique - Habib, Ibrahim Hassan; Rizk, Mohammed Salem; Sultan, Maha; Mohamed, Dalia; Tony, Rehab Moussa (European Journal of Chemistry, 2019)
Cathodic voltammetric behaviors of drospirenone and ethinylestradiol were used for the simultaneous determination of both drugs in bulk and in pharmaceutical formulation (Yasmin® tablets) without the interference of excipients. The determinations were made on hanging mercury dropping electrode using square-wave technique in a voltammetric cell containing 10 mL of 0.04 mole/L Britton-Robinson. After every aliquot addition, the solution was stirred for 10 s at 1000 rpm, rested for 10 s then square wave voltammetry mode was ramped from +100 to -1700 mV with scan rate of 100 mV/s, pulse amplitude of 50 mV and measurement time of 5 ms. Several factors such as pH, type of supporting electrolyte, pulse amplitude and scan rate were studied to optimize the condition for voltammetric determination of these drugs. With optimized experimental parameters, a good linearity was obtained for both drugs over a range of 1.36×10-6 to 1.91×10-7 mole/L and 6.75×10-8 to 6.07×10-7 mol/L of drospirenone and ethinylestradiol, respectively. Characterization of the proposed method was done according to International Conference on Harmonization, Q2B: Validation of Analytical procedures. The proposed method was statistically compared with the reference method and the results revealed no significant difference regarding accuracy and precision.